The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acsami.3c04139
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Photocatalysts: Polyoxometalate Synthons Enable Tailored CdS–MoS2 Morphologies and Enhanced H2 Evolution

Abstract: The development of photocatalysts toward highly efficient H2 evolution reactions is a feasible strategy to achieve the effective conversion of solar energy and meet the increasing demand for new energy. To this end, we prepared two different CdS–MoS2 photocatalysts with unique morphologies ranging from hexagonal prisms to tetragonal nanotubes by carefully tuning polyoxometalate synthons. These two photocatalysts, namely, CdS–MoS2-1 and CdS–MoS2-2, both exhibited remarkable photocatalytic efficiency in H2 gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…CV measurements of CCO and NCS were carried out under different sweep speeds (Figure S5). By observing the image, it can be clearly seen that the CV curve of CCO has a pair of redox peaks in the potential window range of 0–0.45 V, indicating that the specific capacitance is mainly provided by the redox reactions of Co 2+ /Co 3+ /Co 4+ and Cu 2+ /Cu + with OH − ions, which are represented as follows: [2,35] CuCo2O4+2normalH2O+e-2CoOOH+CuOH+OH- $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm CuCo}{_{2}}{\rm O}{_{4}}+{\rm 2H}{_{2}}{\rm O}+{\rm e}{^{- }}\leftrightarrow {\rm 2CoOOH}+{\rm CuOH}+{\rm OH}{^{- }}\hfill\cr}}$ CoOOH+OH-CoO2+H2O+e- $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm CoOOH}+{\rm OH}{^{- }}\leftrightarrow {\rm CoO}{_{2}}+{\rm H}{_{2}}{\rm O}+{\rm e}{^{- }}\hfill\cr}}$ CuOH+OH-Cu(OH)2+e- $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm CuOH}+{\rm OH}{^{- }}\leftrightarrow {\rm Cu}({\rm OH}){_{2}}+{\rm e}{^{- }}\hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…CV measurements of CCO and NCS were carried out under different sweep speeds (Figure S5). By observing the image, it can be clearly seen that the CV curve of CCO has a pair of redox peaks in the potential window range of 0–0.45 V, indicating that the specific capacitance is mainly provided by the redox reactions of Co 2+ /Co 3+ /Co 4+ and Cu 2+ /Cu + with OH − ions, which are represented as follows: [2,35] CuCo2O4+2normalH2O+e-2CoOOH+CuOH+OH- $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm CuCo}{_{2}}{\rm O}{_{4}}+{\rm 2H}{_{2}}{\rm O}+{\rm e}{^{- }}\leftrightarrow {\rm 2CoOOH}+{\rm CuOH}+{\rm OH}{^{- }}\hfill\cr}}$ CoOOH+OH-CoO2+H2O+e- $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm CoOOH}+{\rm OH}{^{- }}\leftrightarrow {\rm CoO}{_{2}}+{\rm H}{_{2}}{\rm O}+{\rm e}{^{- }}\hfill\cr}}$ CuOH+OH-Cu(OH)2+e- $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm CuOH}+{\rm OH}{^{- }}\leftrightarrow {\rm Cu}({\rm OH}){_{2}}+{\rm e}{^{- }}\hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%
“…CV measurements of CCO and NCS were carried out under different sweep speeds (Figure S5). By observing the image, it can be clearly seen that the CV curve of CCO has a pair of redox peaks in the potential window range of 0-0.45 V, indicating that the specific capacitance is mainly provided by the redox reactions of Co 2 + /Co 3 + /Co 4 + and Cu 2 + /Cu + with OH À ions, which are represented as follows: [2,35] CuCo…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Ran et al developed a Si-doped ZnWO 4 @ZnO photocatalyst with a unique morphology from a Keggin POMs@ZIF precursor that acted as an efficient catalyst for degrading Rhodamine B under visible light irradiation . Recently, Sun et al reported the synthesis of CdS-MoS 2 with different morphologies under different synthetic conditions starting from the H 3 PMo 12 O 40 cluster and studied the effects of morphology on their photocatalytic hydrogen evolution activities . These new photocatalysts showed superior performance toward the hydrogen evolution reaction (HER) compared to the conventional CdS.…”
Section: Introductionmentioning
confidence: 99%